Respuesta :

gmany

[tex]\left\{\begin{array}{ccc}x=3y+9\\9-x=-3y\end{array}\right\\\\\text{Substitute from the first equation to the second equation:}\\\\9-(3y+9)=-3y\\\\9-3y-9=-3y\\\\-3y=-3y\qquad\text{add 3y to both sides}\\\\0=0\qquad TRUE\\\\\text{Therefore you answer is}\ \boxed{infinite\ solutions}[/tex]

Answer:

infinite solutions

Step-by-step explanation:

x = 3y+9

9-x=-3y

Substitute x into the second equation

9 - (3y+9) = -3y

Distribute

9-3y-9= -3y

-3y = -3y

Add 3y to each side

-3y+3y = -3y +3y

0=0

This is a true statement always.  When we always have a true statement, we have infinite solutions no matter what the variable is.

We have infinite solutions